Team Management 3.0 : Virtual team management with gamified aspects - Kotoun, Karel (2016)
The aim of this paper is to analyse gamification practices as well as to study management by personalities. Upon this basis the objective will be to design a management software for the new management era that will collect large quantities of data about individual team members (Big Data-based software), thus enabling managers to allocate new team members onto teams upon their personalities, skills and experience in gamified user interface. The ultimate goal of this paper will be to serve as guidebook for managers to manage by knowing the variety of personalities as well as by applying gamification elements onto everyday tasks.